Environmental exposure to TiO2 nanomaterials incorporated in building material. (January 2017) - Bossa, Nathan; Chaurand, Perrine; Levard, Clément; Borschneck, Daniel; Miche, Hélène; Vicente, Jérôme; Geantet, Christophe; Aguerre-Chariol, Olivier; Michel, F. Marc; Rose, Jérôme
Abstract: Nanomaterials are increasingly being used to improve the properties and functions of common building materials. A new type of self-cleaning cement incorporating TiO2 nanomaterials (TiO2 -NMs) with photocatalytic properties is now marketed. This promising cement might provide air pollution-reducing properties but its environmental impact must be validated. During cement use and aging, an altered surface layer is formed that exhibits increased porosity. The surface layer thickness alteration and porosity increase with the cement degradation rate. The hardened cement paste leaching behavior has been fully documented, but the fate of incorporated TiO2 -NMs and their state during/after potential release is currently unknown. In this study, photocatalytic cement pastes with increasing initial porosity were leached at a lab-scale to produce a range of degradation rates concerning the altered layer porosity and thickness. No dissolved Ti was released during leaching, only particulate TiO2 -NM release was detected. The extent of release from this batch test simulating accelerated worst-case scenario was limited and ranged from 18.7 ± 2.1 to 33.5 ± 5.1 mg of Ti/m 2 of cement after 168 h of leaching. TiO2 -NMs released into neutral aquatic media (simulate pH of surface water) were not associated or coated by cement minerals. The TiO2 -NM release mechanism is suspected to start from freeing of TiO2 -NMs in the altered layer pore network due to partial cement paste dissolution followed by diffusion into the bulk pore solution to the surface. The extent of TiO2 -NM release was not solely related to the cement degradation rate. Graphical abstract: Highlights: Photocatalytic cement was predicted to be a minor source for the release of TiO2 -NMs into the environment. Blockage mechanisms (chemical or physical retention) controlling TiO2 -NMs release from cement matrix are suspected. When reaching neutral aquatic media, released TiO2 -NMs were not associated or coated by cementitious minerals. Abstract : When released in surface water, TiO2-NMs appeared to be dissociated from the cement matrix because of the low chemical stability of cement minerals.